Osada wiejska Czerwieńsk w powiecie zielonogórskim w latach 1945-1947 = Czerwieńsk rural settlement of Zielona Gora District during the years 1945-1947 - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Czerwieńsk rural settlement of Zielona Gora District during the years 1945-1947. InFebruary 1945, Czerwieńsk, located north of Zielona Gora and near the Odra River, was occupied by Soviet soldiers of the 3rd Guards Army of the First Ukrainian Front. War damage on these formerly German lands was minor, it was estimated from 2% to 3%. Following the Potsdam Conference, northern and western territories, including Czerwieńsk, became a part of the Polish State.
Keywords: Czerwieńsk; powiat zielonogórski; Polska Partia Robotnicza (PPR); Polskie Stronnictwo Ludowe; Zoń, Ignacy (ksiądz; 1915-1967); Zielona Gora District; Polish Workers` Party; Polish People`s Party